Correction of myocardial ischaemia after transcatheter embolisation of a small left coronary artery venous fistula. Issue 3 (March 1993) - Prakash, A; Reidy, J S; Holt, P M
Abstract : A 50 year old woman presented with a history of angina and palpitation. She had a positive exercise test and thallium scintigraphy showed reversible ischaemia in the territory of the left anterior descending coronary artery. Coronary angiography showed a small coronary arteriovenous fistula arising from the bifurcation of the left main stem–that is, the origin of the left anterior descending and circumflex coronary arteries–with no evidence of coronary stenosis. The aberrant coronary artery was embolised with platinum microcoils delivered by a percutaneous, transcatheter, coaxial technique. The patient was subsequently symptom free with no evidence of ischaemia on exercise testing or thallium scintigraphy. This case suggests that when there is clear evidence of myocardial ischaemia even small coronary arteriovenous fistulas should be treated by embolisation.